Analysis of Some Potentially Toxic Elements (PTEs) (Arsenic, Cadmium, Chromium, Copper, Nickel, Lead and Zinc) in Different Smoked Fishes Sold in Gamawa and Hardawa Markets in Bauchi State, Nigeria - Bappayo, A.M.; Sagagi, B.S. (International Journal of Scientific Research in Biological Sciences, 2021)
The heavy metal contamination of smoked fish species in Bauchi state, Nigeria`s northeastern region, was investigated. Zn, Cd, Cu, As, Ni, Pb, and Cr were detected in smoked fish species collected at random from different parts of the Gamawa and Hardawa markets. The concentrations of potentially toxic elements in samples collected after digestion using a conventional procedure in triplicate were analysed using Microwave Plasma Atomic Emission Spectroscopy (MPAES).The ranges of the measured concentrations in the samples were as follows; Zn (63.17 to 117.51 mg/kg), Cd (0.12 to 0.26 mg/kg), Cu (4.19 to 6.39 mg/kg), As (19.60 to 34.98 mg/kg), Ni (3.45 to 7.88 mg/kg), Pb (0.13 to 9.89 mg/kg) and Cr (3.04 to 8.98). The toxic elements Cd and Zn were the least abundant and most abundant in all nine (9) species, respectively. Cu and Cd levels were within the World Health Organization`s maximum guidelines in this investigation (WHO), except for samples from Gamawa (Catfish (117.50 mg/kg) and Clarias (112.60 mg/kg)) and Hardawa (Tilapia 116.50 mg/kg), the concentrations of Zn were found to be below the acceptable limits. In every smoked fish sample tested, the amounts of As, Ni, Pb, and Cr were greater than the WHO`s maximum tolerable limit. The findings of this study revealed that the fish sold in these markets were substantially contaminated with the PTE (Ni, Pb, As, and Cr), posing a serious health risk to the populace.